Is Portugal really so arteriosclerotic? Results from a cross-country analysis of labor adjustment - John T. Addison; Paulino Teixeira (Zentrum für Europäische Wirtschaftsforschung (ZEW), 1999)
Reputation indexes of employment protection have proven popular constructs in studies of the covariation of labor market institutions and macroeconomic outcomes. Portugal occupies an unenviable rank order in such measures of the stringency of employment protection. We critique this reputation in two ways: first, by offering a modicum of 'corrective' institutional detail on the nature of employment protection in Portugal; and, second, and more substantively, by offering a detailed analysis of the process of labor djustment in Portugal, benchmarked to other-country experience. The latter exercise – based on a two- and one-stage error correction model – reveals Portugal to have a very high speed of adjustment to deviations from the long-run employment-output equilibrium – a result that is clearly at odds with its allegedly sclerotic labor market. More in accord with received wisdom is the very smooth labor adjustment mechanism characterizing the United Kingdom. The most notable feature of the German results is the deterioration in that country's speed of adjustment in recent years. The Spanish case is distinguished by its erratic path of long-run adjustment.
Keywords: 330; Arbeitsmarktflexibilisierung; Arbeitsrecht; Wirtschaftliche Anpassung; Arbeitsmarkt; Beschäftigungseffekt; Schätzung; Portugal; Deutschland; Spanien; Großbritannien